Cortical auditory evoked potentials using the speech stimulus /ma - Macambira,Ysa Karen dos Santos (2022)
ABSTRACT Purpose: to compare cortical auditory evoked responses using two speech stimuli, /ma/ and /da/, in normally hearing young adults. Methods: a cross-sectional, observational and analytical study, with a sample composed of nineteen normally hearing young adults, recruited by convenience, ages between 18 and 25 years old, from both genders, participated in the study. Cortical auditory evoked potentials (CAEP) were monaurally recorded in two conditions: 1) with a pair of speech stimuli /ba/ and /da/, and 2), with a pair of speech stimuli /ba/ and /ma/. The order of the experiments was randomized in a proportion of 50% for each of the two stimuli, totaling 100 stimuli for each experiment. Speech sounds were presented at 70 dB SPL. Descriptive and analytical statistical tests were performed. Results: mean latency values of the complex P1, N1, P2, N2 and P3 were lower for the /ma/ when compared to those of /da/ (p <0,05). There was no difference in amplitude values between responses evoked using /ma/ and /da/. Conclusion: cortical auditory evoked potentials, elicited by the speech stimulus /ma/ had, on average, lower latency peaks of P1-N1-P2-N2 and P3, when compared to those of speech stimulus /da/.